Galanin N-terminal fragment (1-15) reduces alcohol consumption in the self-administration with involvement of mesocorticolimbic system in rats. - Cantero-García, Noelia; Flores Gómez, Marta; Flores-Burgess, Antonio; Pineda-Gómez, Juan Pedro; Orio, Laura; Serrano, Antonia; Díaz-Cabiale, Zaida; Millón-Peñuela, Carmelo (My University, 2023)
Alcohol Use Disorder (AUD) is a highly prevalent disorder characterized by an impaired ability tostop or control alcohol use despite the adverse consequences. Nowadays, AUD treatment is limiteddue to the low efficacy of the medication. Our research group discovered that GAL(1–15) induces asubstantial reduction in preference and voluntary alcohol consumption in rats. To investigate therole of GAL(1-15) in alcohol seeking-behaviour, we used the self-administration in rats. Also, weanalyzed the mesocorticolimbic system on the mRNA expression. Male Sprague-Dawley rats (n=6-15 animals in each group) were trained to self-administer 10%alcohol under fixed-ratio FR1 in the self-administration boxes. GAL(1-15) or vehicle wereadministered intracerebroventricular 15 min before the test. A dose-response of GAL(1-15) at doses0.3, 1 and 3nmol was performed in the alcohol self-administration test. GALR1 and GALR2 wereanalyzed with GALR2 antagonist M871 and using an in vivo model siRNA GALR1 or GALR2knockdown rats. We analyzed mRNA expression of C-Fos in the ventral tegmental area (VTA),accumbens nucleus (NAc) and prefrontal cortex (PFC). One-way ANOVA followed by Fisher´s leastsignificant difference test was used. GAL(1-15) 3nmol reduced the number of reinforcements and the active lever (p<0.01) comparedwith control animals. GAL(1-15) 1nmol induced a less strong but significant reduction in thisparameters.The M871 3nmol blocked the GAL(1-15)-induced reduction in the number ofreinforcements and in the number of active lever (p<0.05). Downregulation of GALR1 or GALR2 bysiRNA was sufficient to block GAL(1-15) effects in this test.GAL(1-15) 3nmol increased mRNA C-Foslevels in VTA (p<0.01), NAc (p<0.05) and PFC(p<0.05) compared with control group. Our results indicate that GAL(1-15) induces a strong reduction of alcohol-seeking behaviour withthe involvement of the mesocorticolimbic pathway and open up the possibility of using GAL(1-15)fragment as a novel pharmacological strategy in AUD
Keywords: Neuropéptidos; Alcoholismo; Alcohol; Galanin(1-15); Alcohol seeking